Overactive bladder: Symptom complex or separate entity? - Herschorn, Sender (Canadian Urological Association Journal, 2013)
In addition to the series of lectures summarized in the articles on the preceding pages, the 2011 Canadian Urology Forum also included a series of workshops intended to help answer the question: “Does overactive bladder (OAB) exist as a separate entity or is it a symptom complex that may be associated with other conditions?” In an effort to arrive at an answer to this question, the participants were divided into groups and asked to examine a particular subset of patients with OAB. The subsets were: females, males, neurogenic and elderly. In each of these workshops, the participants were asked to answer the following questions: • What is the most likely underlying cause? • Are there unique phenotypes that can be identified clinically that are linked to a common underlying pathophysiology? • What is the likelihood of associated disorders of the outlet or pelvic floor? • What are the most effective treatments? Each of the groups then reported their answers back to the entire group of participants, after which time they were asked to vote on the key question. This review provides a summary of the discussions that took place in each group and concludes with the results of the vote.